Reform, Radicalism, and the Role of Islam in Modern Societies (American Journal of Islam and Society, 2012)
These three books cover the common themes of the last century and ahalf of Muslim activism ‒ reform, radicalism, and the role of Islam inmodern societies. Each book covers a different phase in the history ofIslamic revivals and their interactions with modernity. John Calvert’sbook is a study of Sayyid Qutb’s work during the phase of the heightenedCold War ideological contestations in the postcolonial period, bothin the Muslim lands as well as globally. Kai Hafez’s book focuses largelyon the last several decades when the study of democracy and democratizationcame to the forefront of the academic/policy scene in the West‒ but also among the Muslim activists. Finally, John Esposito’s book spotlightsthe Muslim present and its possible futures. Combined, the booksprovide an overview of the important issues surrounding Muslim activismand possibilities for political and religious reform among the Muslims ...